Growth and Quality Analysis of Baby Corn (Zea mays L.) and Fodder as Influenced by NPK and Zn Fertility under Varying Spatial Geometry in Indo-Gangetic Plain Zone of Bihar - Sharma, Alka Jyoti; Singh, Mahesh Kumar; Kumar, Sanjay; Acharya, Shivasankar; Shambhavi, Shweta; Sneha (International Journal of Economic Plants, 2024)
A field experiment was conducted during the kharif season (June–August, 2018) at Bihar Agricultural University, Sabour, Bihar, India, to assess the growth and quality of baby corn as influenced by NPK and zinc fertility approaches under varying spatial geometries in Indo-gangetic plain zone of Bihar. The experiment was laid out in split-split-plot design with three levels of spatial geometry, viz. 40×20 cm2 spacing, 50×15 cm2 spacing and paired row planting (30 cm spacing in between two lines in a paired-row; 50 cm between the two paired-rows and 10 cm between plants within a row) in main plot; three levels of fertility viz. 120:60:60, 150:75:75 and 180:90:90 kg N:P2O5:K2O ha-1 in sub-plots; and two levels of zinc viz., 2.5 and 5.0 kg Zn ha-1 in sub-sub plots, replicated thrice. Paired row planting recorded enhanced and significant increase in growth attributes, thereby registering highest baby corn yield (1.43 t ha-1), green fodder yield (26.78 t ha-1) and dry fodder yield (11.46 t ha-1), as compared to conventional planting. 180:90:90 kg N:P2O5:K2O ha-1 and 5.0 kg Zn ha-1 enhanced the growth parameters as well as baby corn, green fodder and dry fodder yield. Paired row planting, NPK fertility @180:90:90 kg N:P2O5:K2O ha-1 and Zn fertility levels @5.0 kg Zn ha-1 also recorded improvement in reducing sugar, protein and zinc content of baby corn as well as nutritional quality of fodder.